Compositions of the essential oils from two types of ocimum basilicum introduced in Bangladesh - Chowdhury, JU; Bhuiyan, MNH; Saha, GC; Nada, K; Rahim, M (Bangladesh Journal of Scientific and Industrial Research, 2013)
Essential oils from two types of Ocimum basilicum introduced in Bangladesh were analyzed by GC-MS. The major constituents found in the oil collected from Indian variety were methyl chavicol (78.2), citral (3.7%) and tau-cadinol (2.49%). Introduced variety from Thailand contains anisole, p-propenyl (93.99%) as major compound. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17335 Bangladesh J. Sci. Ind. Res. 48(3), 217-220, 2013